2008
DOI: 10.1345/aph.1k447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carvedilol on the Serum Lipid Profile

Abstract: It is clear that beta(1)-selective antagonists worsen the lipid profile compared with carvedilol. However, it is unclear whether carvedilol independently makes an improvement or has a neutral effect on the lipid profile. Carvedilol should be an important treatment consideration in patients with heart failure and/or hypertension with dyslipidemia. However, many questions remain regarding this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…8,9 A recent review showed that carvedilol did not adversely affect plasma lipids compared to β1-selective agents. 33 The results of the main study from which these samples were tested have been published and are concordant with previous findings 17 . In our investigation, we found a treatment interaction with the Arg16Gly polymorphism and β-blocker therapy on changes in triglycerides levels, showing increased triglycerides with metoprolol when participants carried the Arg16Arg genotype.…”
Section: Discussionsupporting
confidence: 88%
“…8,9 A recent review showed that carvedilol did not adversely affect plasma lipids compared to β1-selective agents. 33 The results of the main study from which these samples were tested have been published and are concordant with previous findings 17 . In our investigation, we found a treatment interaction with the Arg16Gly polymorphism and β-blocker therapy on changes in triglycerides levels, showing increased triglycerides with metoprolol when participants carried the Arg16Arg genotype.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the beneficial vasodilatory effects mediated via nitric oxide may contribute to the clinical findings with nebivolol and carvedilol. Improvements in endothelial effects have also been hypothesized to contribute to the apparently improved adverse event profileparticularly related to metabolic effects and sexual dysfunction -of vasodilating beta-blockers compared with older agents in this class [62][63][64][65][66]. For example, a recent study [67] showed that nebivolol, but not metoprolol, improved the endothelial function of the corpus cavernosum in apolipoprotein E-knockout mice.…”
Section: Clinical Implications and Future Issuesmentioning
confidence: 99%
“…A post hoc analysis of the Glycemic Effects in Diabetes Mellitus: CarvedilolMetoprolol Comparison in Hypertensives (GEMINI) trial showed favorable lipid effects of carvedilol compared to metoprolol in over 1200 subjects with diabetes [9]. Sharp et al [10] analyzed 12 carvedilol studies, 6 of which compared carvedilol with selective beta 1-adrenergic antagonists and found that carvedilol had either a neutral or a mild beneficial effect on serum lipids. This difference may be due to the alpha 1-antagonist action as alpha-adrenergic blockers such as prazosin have been consistently shown to reduce serum triglycerides and increase HDL cholesterol [2,11,12].…”
Section: Beta-adrenergic Blockersmentioning
confidence: 99%